A powder coating for electric drive system of new energy vehicle and preparation method thereof
By using modified epoxy resin and modified boron nitride, combined with aluminate coupling agent and heptadecyl trimethoxysilane, the problem of poor compatibility between boron nitride and epoxy resin is solved, and the moisture-heat resistance and thermal stability of powder coatings for electric drive systems in new energy vehicles is significantly improved.
Patent Information
- Application Number
- CN202411294886.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-14
- Publication Date
- 2025-04-01
- Estimated Expiration
- 2044-09-14
AI Technical Summary
Among the insulated anti-aging powder coatings used in the electric drive systems of existing new energy vehicles, boron nitride has poor compatibility with epoxy resin, resulting in defects inside the coating, affecting the mechanical properties and overall quality.
Modified epoxy resin and modified boron nitride are used as the main raw materials, boron nitride is modified by aluminate coupling agent, and heptadec-fluorodecyl trimethoxysilane is added to the composite filler to improve the hydrophobic properties of the composite filler, thereby improving the moisture-heat resistance of the powder coating.
The impact resistance, humidity and heat resistance, thermal stability and flame retardancy of powder coatings for electric drive systems of new energy vehicles have been significantly improved, and the overall performance of the material has been enhanced.
Smart Images

Figure SMS_1 
Figure SMS_2
Abstract
Description
Technical Field
[0001] This invention relates to the field of powder coating technology, specifically to a powder coating for electric drive systems of new energy vehicles and its preparation method. Background Technology
[0002] With the rapid development of the new energy vehicle industry, higher requirements have been placed on the reliability and durability of electric drive systems. The insulating materials in electric drive systems not only need to provide good electrical insulation performance but also possess excellent anti-aging properties to ensure the long-term stable operation of the entire system. Powder coatings, as a commonly used insulating material, have been widely applied in new energy vehicle electric drive systems due to their environmental friendliness and high efficiency.
[0003] Currently, there are several insulating and anti-aging powder coatings available on the market for electric drive systems in new energy vehicles. To improve the anti-aging performance of these coatings, researchers typically add boron nitride (BN) as a filler to the epoxy resin matrix. Boron nitride possesses good thermal stability, high thermal conductivity, and excellent electrical insulation properties, which can significantly improve the anti-aging performance of the coating. However, the poor compatibility between boron nitride and epoxy resin is a problem that urgently needs to be solved. Boron nitride particles are prone to agglomeration in the epoxy resin matrix, leading to defects within the coating and thus affecting the mechanical properties and overall quality of the final product.
[0004] Therefore, the applicant developed a powder coating for electric drive systems of new energy vehicles to solve the above problems. Summary of the Invention
[0005] To address the existing technical problems, this invention provides a powder coating for electric drive systems of new energy vehicles. By weight, the raw material components include: 50-80 parts of composite epoxy resin, 10-20 parts of composite filler, 2-4 parts of curing agent, 0.2-0.8 parts of imidazole accelerator, 1-2 parts of leveling agent, 0.8 parts of wax powder, 0.3-0.9 parts of benzoin, and 1-5 parts of pigment.
[0006] The leveling agent is polyether-modified polydimethylsiloxane;
[0007] The curing agent is latent dicyandiamide;
[0008] The catalyst is an imidazole-based promoter.
[0009] Furthermore, the composite epoxy resin is obtained by mixing and reacting 2-amino-4-hydroxy-6-methylpyrimidine, hexamethylene diisocyanate trimer, 4-aminophenylboronic acid pinacol ester, and epoxy resin; the epoxy resin is E51 type epoxy resin with an average epoxy value of 0.51 and an average hydroxyl value of 0.046; by introducing 4-aminophenylboronic acid pinacol ester into the epoxy resin, not only can the thermal stability of the epoxy resin be improved, but its mechanical properties can also be enhanced; in addition, this introduction can also adjust the chemical properties of the epoxy resin, giving it specific functionalities, such as flame retardancy and special reactivity, because the phenylboronic acid group has good flame retardant properties.
[0010] Furthermore, the composite filler is obtained by mixing and reacting aluminum isopropoxide, ethyl acetoacetate, ethanol, modified boron nitride, and a silane coupling agent.
[0011] Furthermore, the modified boron nitride is boron nitride modified with an aluminate coupling agent;
[0012] Furthermore, the silane coupling agent is heptadecafluorodecyltrimethoxysilane;
[0013] Furthermore, the aluminate coupling agent is isopropyl distearate aluminate;
[0014] Hexagonal boron nitride is a material with excellent thermal and chemical stability. Its layered structure is similar to graphite, but it has insulating properties. When hexagonal boron nitride is used to prepare composite fillers and mixed with modified epoxy resin, its thermal conductivity, wear resistance, mechanical properties, thermal stability, and anti-aging properties can be improved.
[0015] This invention also provides a method for preparing powder coatings for electric drive systems of new energy vehicles, comprising the following preparation steps:
[0016] Add 50-80 parts by weight of modified epoxy resin to a sand mill dispersion mixer, add 10% hydrochloric acid solution to pH 1, disperse at 2000-3000 r / min for 1 hour, then continue to add 25% NaOH solution dropwise until pH 13, continue dispersing for 1 hour, let stand, remove the supernatant, then continue to add hydrochloric acid, 10% hydrochloric acid solution until pH 5, evaporate to dryness, and add together with 10-20 parts by weight of composite filler to the sand mill dispersion mixer, and heat. Disperse the powder at 2000-3000 r / min for 8 hours at 80℃. After naturally cooling to room temperature, add 2-4 parts by weight of curing agent, 0.2-0.8 parts by weight of imidazole accelerator, 1-2 parts by weight of leveling agent, 0.8 parts by weight of wax powder, 0.3-0.9 parts by weight of benzoin, and 1-5 parts by weight of pigment. Continue dispersing for 30 minutes. Then, extrude the powder using a twin-screw extruder. After cooling and crushing, pulverize the powder using a high-speed pulverizer and pass it through a 180-mesh standard sieve to obtain powder coating for electric drive systems of new energy vehicles.
[0017] Further, the preparation method of the modified epoxy resin is as follows: Under nitrogen protection and anhydrous conditions, 2-amino-4-hydroxy-6-methylpyrimidine and hexamethylene diisocyanate trimer are mixed in a molar ratio of 1:1, then heated to 60°C, and vacuumed at a stirring speed of 150 rpm until no bubbles are generated on the liquid surface. The temperature is then raised to 90°C and stirred for 26 hours. After cooling to room temperature, 20-40 times the mass of 2-amino-4-hydroxy-6-methylpyrimidine in n-hexane is added, and the mixture is stirred at room temperature for 4-6 hours. The mixture is then filtered using a sand core filter. The resulting filter residue is washed with n-hexane, and the above operation is repeated until no hexamethylene diisocyanate residue remains in the filtrate. The filter residue is then mixed with 4-aminophenylboronic acid pinacol ester and chloroform, wherein the molar ratio of hexamethylene diisocyanate trimer to 4-aminophenylboronic acid pinacol ester is 1:1, and the molar ratio of chloroform to... The filter residue was mixed at a mass ratio of 1.7–1.9:15–16 and stirred at 60°C for 12 hours. After cooling to room temperature, it was vacuum filtered using a sand core filter to obtain secondary filter residue. The secondary filter residue and chloroform were mixed evenly at a mass ratio of 1:50–60. Then, E51 epoxy resin was added, with the molar ratio of hydroxyl groups in the epoxy resin to isocyanates in the secondary filter residue being 1:1–1.2. Dibutyltin dilaurate (0.1 times the mass of the secondary filter residue) was added, and the mixture was stirred and refluxed at 60°C for 24 hours. After naturally cooling to room temperature, chloroform (100 times the mass of the secondary filter residue) was added and diluted. The mixture was allowed to stand for 12 hours. The lower layer solution was removed, and chloroform (150 times the mass of the secondary filter residue) was added and allowed to stand for 24 hours. The lower layer solution was removed again, and this process was repeated 5 times. The remaining solution was then evaporated using a rotary evaporator to remove the chloroform solvent, yielding modified epoxy resin.
[0018] Furthermore, the preparation method of the composite filler is as follows: At 25°C, aluminum isopropoxide, ethyl acetoacetate, and ethanol are ultrasonically mixed in a molar ratio of 1:1:5 for 10 min. The mixture is then poured into 85°C hot water at a speed of 250-300 r / min, which is 200 times the amount of aluminum isopropoxide. The temperature and stirring speed are kept constant. After stirring for 30 min, the pH value is adjusted to 3.2-3.5 by adding 68% nitric acid. The mixture is then allowed to cool naturally to room temperature. Next, isopropanol is added in a volume 1.5 times the amount of aluminum isopropoxide. Stirring continues, followed by the sequential addition of modified boron nitride and silane coupling agent. The molar ratio of aluminum isopropoxide to silane coupling agent is 1:3, and the mass ratio of aluminum isopropoxide to modified boron nitride is 1:0.2-0.4. Stirring continues for 2-4 h to obtain the composite filler.
[0019] Furthermore, the modified boron nitride is prepared as follows: hydroxylated boron nitride is added to a high-speed mixer and stirred at 1500-2000 rpm for 20-40 min at 75°C. Then, an aluminate coupling agent is added and stirring is continued for 2-4 h to obtain modified boron nitride.
[0020] Furthermore, the mass ratio of the aluminate coupling agent to the hydroxylated boron nitride is 0.01 to 0.03:1.
[0021] Furthermore, the preparation method of the hydroxylated boron nitride is as follows: hexagonal boron nitride powder and sodium cholate powder are added to deionized water and mixed, wherein the mass ratio of hexagonal boron nitride powder, sodium cholate powder and deionized water is 1:0.01:40. Then, the mixture is placed in an ultrasonic cell disruptor and treated with ultrasound at 600W for 2.5 to 3.5 hours. After the ultrasound is completed, the mixture is centrifuged at 3000 r / min for 8 to 12 minutes. The bottom precipitate is then removed, and the upper suspension is taken and dried in an oven at 60°C to obtain hydroxylated boron nitride.
[0022] Compared with the prior art, the beneficial effects of the present invention are as follows:
[0023] The powder coating for electric drive systems of new energy vehicles prepared by this invention comprises, by weight, the following raw material components: 50-80 parts of composite epoxy resin, 10-20 parts of composite filler, 2-4 parts of curing agent, 0.2-0.8 parts of imidazole accelerator, 1-2 parts of leveling agent, 0.8 parts of wax powder, 0.3-0.9 parts of benzoin, and 1-5 parts of pigment; the composite epoxy resin is obtained by mixing and reacting 2-amino-4-hydroxy-6-methylpyrimidine, hexamethylene diisocyanate trimer, 4-aminophenylboronic acid pinacol ester, and epoxy resin; the composite filler is obtained by mixing and reacting aluminum isopropoxide, ethyl acetoacetate, ethanol, modified boron nitride, and silane coupling agent; the modified boron nitride is aluminate coupling agent modified boron nitride.
[0024] First, modified boron nitride was prepared by reacting an aluminate coupling agent with hydroxylated boron nitride. After hydrolysis, the aluminate coupling agent reacted with the hydroxyl groups on the surface of boron nitride to condense and coat the surface of boron nitride. Then, the modified boron nitride was uniformly dispersed in an alumina sol obtained by mixing aluminum isopropoxide, ethyl acetoacetate, and ethanol to increase the compatibility between boron nitride and alumina sol. At the same time, heptadecafluorodecyltrimethoxysilane was added to the alumina sol to improve the hydrophobic properties of the composite filler, thereby improving the damp heat resistance of the powder coating for electric drive systems of new energy vehicles.
[0025] Secondly, the composite epoxy resin is obtained by mixing and reacting 2-amino-4-hydroxy-6-methylpyrimidine, hexamethylene diisocyanate trimer, 4-aminophenylboronic acid pinacol ester, and epoxy resin. The amino groups on 2-amino-4-hydroxy-6-methylpyrimidine and 4-aminophenylboronic acid pinacol ester react with some of the isocyanates on the hexamethylene diisocyanate trimer. The remaining isocyanate groups react with the hydroxyl groups in the epoxy resin to form a composite epoxy resin with an epoxy resin molecular chain as the main chain and UPy groups, a six-membered heterocycle of isocyanurate, and phenylboronic acid pinacol ester as the side chain. This enhances the composite epoxy resin's properties. The toughness of epoxy resin is enhanced by the introduction of the UPy structure containing quadruple hydrogen bonds into the composite epoxy resin molecular chain. The quadruple hydrogen bonds between the UPy groups act as physical cross-linking points, effectively "increasing" the cross-linking density of the composite epoxy resin. Furthermore, during the stretching process, the breaking of the quadruple hydrogen bonds formed between the UPy groups consumes some energy, and the introduction of the flexible side chains increases the sliding resistance between them, thereby enhancing the tensile strength and elongation at break of the composite epoxy resin, and ultimately improving the impact resistance of the powder coating for electric drive systems of new energy vehicles.
[0026] Finally, the composite epoxy resin and composite filler are mixed. The -(CH2)16CH3 functional group on the isopropyl distearate aluminate in the composite filler is intertwined with the molecular chains on the composite epoxy resin. To break the intertwined structure, more heat needs to be absorbed, ensuring the thermal stability of the powder coating for the electric drive system of new energy vehicles. The phenylboronic acid pinacol ester in the composite epoxy resin is hydrolyzed to obtain phenylboronic acid. Benzeneboronic acid reacts with the silanol in the composite filler to form polysiloxane, which firmly connects the composite epoxy resin and composite filler together. The Si-OBO segments in its molecular structure are flexible segments that are easily plastically deformed under external force, thus enhancing the strength of the composite epoxy resin. The PBSi material exhibits high elongation at break due to the slippage ability between molecular chains. Furthermore, the Si-OBO structure in the PBSi molecular structure provides excellent thermal stability. Simultaneously, the hydrophobic Si-O bonds in PBSi have lower surface energy than CH bonds, which helps reduce the surface energy of the PLA film and decrease its contact area with water, thereby increasing the interfacial energy and transforming the material into a hydrophobic material. This further enhances the impact resistance and damp heat resistance of the insulating and anti-aging powder coating. Additionally, the polysiloxane and boron nitride in the composite filler form a thermally conductive network, enhancing the thermal conductivity of the composite epoxy resin. Detailed Implementation
[0027] The present invention will be further described in detail below with reference to embodiments, but the following embodiments should not be construed as limiting the present invention.
[0028] The following are some of the raw materials used in the embodiments and comparative examples of this invention:
[0029] The epoxy resin used is E51 type epoxy resin, with an average epoxy value of 0.51 and an average hydroxyl value of 0.046.
[0030] Example 1
[0031] A method for preparing powder coating for electric drive systems of new energy vehicles, comprising the following steps:
[0032] 50 parts by weight of modified epoxy resin were added to a sand mill dispersion mixer. 10% hydrochloric acid solution was added until the pH reached 1, and the mixture was dispersed at 2000 r / min for 1 hour. Then, 25% NaOH solution was added dropwise until the pH reached 13, and the mixture was dispersed for another hour. After standing, the supernatant was removed. Then, hydrochloric acid and 10% hydrochloric acid solution were added until the pH reached 5. After rotary drying, the mixture was added to the sand mill dispersion mixer along with 10 parts by weight of composite filler. The mixture was heated to 80℃ and dispersed at 2000 r / min for 8 hours. After naturally cooling to room temperature, 2 parts by weight of curing agent, 0.2 parts by weight of imidazole accelerator, 1 part by weight of leveling agent, 0.8 parts by weight of wax powder, 0.3 parts by weight of benzoin, and 1 part by weight of pigment were added. The mixture was dispersed for another 30 minutes. Then, the mixture was extruded using a twin-screw extruder. After cooling and crushing, the mixture was pulverized using a high-speed pulverizer and passed through a 180-mesh standard sieve to obtain a powder coating for electric drive systems of new energy vehicles.
[0033] The modified epoxy resin is prepared as follows: Under nitrogen protection and anhydrous conditions, 2-amino-4-hydroxy-6-methylpyrimidine and hexamethylene diisocyanate trimer are mixed in a molar ratio of 1:1, then heated to 60°C, and vacuumed at a stirring speed of 150 rpm until no bubbles are generated on the liquid surface. The temperature is then raised to 90°C and stirred for 26 hours. After cooling to room temperature, 20 times the mass of n-hexane (based on the mass of 2-amino-4-hydroxy-6-methylpyrimidine) is added and stirred at room temperature for 4 hours. The mixture is then filtered using a sand filter. The resulting filter residue is washed with n-hexane, and the above operation is repeated until no hexamethylene diisocyanate residue remains in the filtrate. The filter residue is then mixed with 4-aminophenylboronic acid pinacol ester and chloroform, wherein the molar ratio of hexamethylene diisocyanate trimer to 4-aminophenylboronic acid pinacol ester is 1:1. The mixture of epoxy resin and filter residue was stirred at 60°C for 12 hours. After cooling to room temperature, it was vacuum filtered using a sand core filter to obtain secondary filter residue. The secondary filter residue and chloroform were mixed evenly at a mass ratio of 1:50. Then, E51 epoxy resin was added, with the molar ratio of hydroxyl groups in the epoxy resin to isocyanates in the secondary filter residue being 1:1. Dibutyltin dilaurate (0.1 times the mass of the secondary filter residue) was added, and the mixture was stirred and refluxed at 60°C for 24 hours. After naturally cooling to room temperature, chloroform (100 times the mass of the secondary filter residue) was added and diluted. The mixture was allowed to stand for 12 hours. The lower layer solution was removed, and chloroform (150 times the mass of the secondary filter residue) was added and allowed to stand for 24 hours. The lower layer solution was removed again, and this process was repeated 5 times. The remaining solution was then evaporated using a rotary evaporator to remove the chloroform solvent, yielding the modified epoxy resin.
[0034] The composite filler is prepared as follows: At 25°C, aluminum isopropoxide, ethyl acetoacetate, and ethanol are ultrasonically mixed in a molar ratio of 1:1:5 for 10 min. The mixture is then poured into 85°C hot water at a speed of 250 r / min, which is 200 times the amount of aluminum isopropoxide. The temperature and stirring speed are kept constant. After stirring for 30 min, the pH value is adjusted to 3.2 by adding 68% nitric acid. The mixture is then allowed to cool naturally to room temperature. Next, isopropanol is added in a volume 1.5 times the amount of aluminum isopropoxide. Stirring continues, followed by the sequential addition of modified boron nitride and silane coupling agent. The molar ratio of aluminum isopropoxide to silane coupling agent is 1:3, and the mass ratio of aluminum isopropoxide to modified boron nitride is 1:0.2. Stirring continues for 2 h to obtain the composite filler.
[0035] The modified boron nitride is prepared as follows: hydroxylated boron nitride is added to a high-speed mixer and stirred at 1500 rpm for 20 min at 75 °C. Then, an aluminate coupling agent is added and stirring is continued for 2 h to obtain modified boron nitride.
[0036] The mass ratio of the aluminate coupling agent to the hydroxylated boron nitride is 0.01:1.
[0037] The preparation method of the hydroxylated boron nitride is as follows: Hexagonal boron nitride powder and sodium cholate powder are added to deionized water and mixed, wherein the mass ratio of hexagonal boron nitride powder, sodium cholate powder and deionized water is 1:0.01:40. Then, the mixture is placed in an ultrasonic cell disruptor and treated with ultrasound at 600W for 2.5 hours. After the ultrasound is completed, the mixture is centrifuged at 3000r / min for 8 minutes. The bottom precipitate is then removed, and the upper suspension is taken and dried in an oven at 60℃ to obtain hydroxylated boron nitride.
[0038] Example 2
[0039] A method for preparing powder coating for electric drive systems of new energy vehicles, comprising the following steps:
[0040] 65 parts by weight of modified epoxy resin were added to a sand mill dispersion mixer. 10% hydrochloric acid solution was added until the pH reached 1, and the mixture was dispersed at 2500 r / min for 1 hour. Then, 25% NaOH solution was added dropwise until the pH reached 13, and the mixture was dispersed for another hour. After standing, the supernatant was removed. Then, hydrochloric acid and 10% hydrochloric acid solution were added until the pH reached 5. After rotary drying, the mixture was added to the sand mill dispersion mixer along with 15 parts by weight of composite filler. The mixture was heated to 80℃ and dispersed at 2500 r / min for 8 hours. After naturally cooling to room temperature, 3 parts by weight of curing agent, 0.5 parts by weight of imidazole accelerator, 1.5 parts by weight of leveling agent, 0.8 parts by weight of wax powder, 0.6 parts by weight of benzoin, and 3 parts by weight of pigment were added. The mixture was dispersed for another 30 minutes. Then, the mixture was extruded using a twin-screw extruder. After cooling and crushing, the mixture was pulverized using a high-speed pulverizer and passed through a 180-mesh standard sieve to obtain a powder coating for electric drive systems of new energy vehicles.
[0041] The modified epoxy resin is prepared as follows: Under nitrogen protection and anhydrous conditions, 2-amino-4-hydroxy-6-methylpyrimidine and hexamethylene diisocyanate trimer are mixed in a molar ratio of 1:1, then heated to 60°C, and vacuumed at a stirring speed of 150 rpm until no bubbles are generated on the liquid surface. The temperature is then raised to 90°C and stirred for 26 hours. After cooling to room temperature, hexane (30 times the mass of 2-amino-4-hydroxy-6-methylpyrimidine) is added and stirred at room temperature for 5 hours. The mixture is then filtered using a sand filter. The resulting filter residue is washed with hexane, and the above operation is repeated until no hexamethylene diisocyanate residue remains in the filtrate. The filter residue is then mixed with pinacol 4-aminophenylboronic acid and chloroform, wherein the molar ratio of hexamethylene diisocyanate trimer to pinacol 4-aminophenylboronic acid is 1:1, and the molar ratio of chloroform to... The filter residue was mixed at a mass ratio of 1.8:15.5 and stirred at 60℃ for 12 hours. After cooling to room temperature, it was vacuum filtered using a sand core filter to obtain secondary filter residue. The secondary filter residue and chloroform were mixed evenly at a mass ratio of 1:55. Then, E51 epoxy resin was added, with a molar ratio of hydroxyl groups in the epoxy resin to isocyanates in the secondary filter residue of 1:1.1. Dibutyltin dilaurate (0.1 times the mass of the secondary filter residue) was added, and the mixture was stirred and refluxed at 60℃ for 24 hours. After naturally cooling to room temperature, chloroform (100 times the mass of the secondary filter residue) was added and diluted. The mixture was allowed to stand for 12 hours. The lower layer solution was removed, and chloroform (150 times the mass of the secondary filter residue) was added and allowed to stand for 24 hours. The lower layer solution was removed again, and this process was repeated 5 times. The remaining solution was then evaporated using a rotary evaporator to remove the chloroform solvent, yielding modified epoxy resin.
[0042] The composite filler is prepared as follows: At 25°C, aluminum isopropoxide, ethyl acetoacetate, and ethanol are ultrasonically mixed in a molar ratio of 1:1:5 for 10 min. The mixture is then poured into 85°C hot water at a speed of 280 r / min, which is 200 times the amount of aluminum isopropoxide. The temperature and stirring speed are kept constant. After stirring for 30 min, the pH value is adjusted to 3.3 by adding 68% nitric acid. The mixture is then allowed to cool naturally to room temperature. Next, isopropanol is added in a volume 1.5 times the amount of aluminum isopropoxide. Stirring continues, followed by the sequential addition of modified boron nitride and silane coupling agent. The molar ratio of aluminum isopropoxide to silane coupling agent is 1:3, and the mass ratio of aluminum isopropoxide to modified boron nitride is 1:0.3. Stirring continues for 3 h to obtain the composite filler.
[0043] The modified boron nitride is prepared as follows: hydroxylated boron nitride is added to a high-speed mixer and stirred at 1800 rpm for 30 min at 75 °C. Then, an aluminate coupling agent is added and stirring is continued for 3 h to obtain modified boron nitride.
[0044] The mass ratio of the aluminate coupling agent to the hydroxylated boron nitride is 0.02:1.
[0045] The preparation method of the hydroxylated boron nitride is as follows: Hexagonal boron nitride powder and sodium cholate powder are added to deionized water and mixed, wherein the mass ratio of hexagonal boron nitride powder, sodium cholate powder and deionized water is 1:0.01:40. Then, the mixture is placed in an ultrasonic cell disruptor and treated with ultrasound at 600W for 3 hours. After the ultrasound is completed, the mixture is centrifuged at 3000r / min for 10 minutes. The bottom precipitate is then removed, and the upper suspension is taken and dried in an oven at 60℃ to obtain hydroxylated boron nitride.
[0046] Example 3
[0047] A method for preparing powder coating for electric drive systems of new energy vehicles, comprising the following steps:
[0048] 80 parts by weight of modified epoxy resin were added to a sand mill dispersion mixer. 10% hydrochloric acid solution was added until the pH reached 1, and the mixture was dispersed at 3000 r / min for 1 hour. Then, 25% NaOH solution was added dropwise until the pH reached 13, and the mixture was dispersed for another hour. After standing, the supernatant was removed. Then, hydrochloric acid and 10% hydrochloric acid solution were added until the pH reached 5. After rotary drying, the mixture was added to the sand mill dispersion mixer along with 20 parts by weight of composite filler. The mixture was heated to 80℃ and dispersed at 3000 r / min for 8 hours. After naturally cooling to room temperature, 4 parts by weight of curing agent, 0.8 parts by weight of imidazole accelerator, 2 parts by weight of leveling agent, 0.8 parts by weight of wax powder, 0.9 parts by weight of benzoin, and 5 parts by weight of pigment were added. The mixture was dispersed for another 30 minutes. Then, the mixture was extruded using a twin-screw extruder. After cooling and crushing, the mixture was pulverized using a high-speed pulverizer and passed through a 180-mesh standard sieve to obtain a powder coating for electric drive systems of new energy vehicles.
[0049] The modified epoxy resin is prepared as follows: Under nitrogen protection and anhydrous conditions, 2-amino-4-hydroxy-6-methylpyrimidine and hexamethylene diisocyanate trimer are mixed in a molar ratio of 1:1, then heated to 60°C, and vacuumed at a stirring speed of 150 rpm until no bubbles are generated on the liquid surface. The temperature is then raised to 90°C and stirred for 26 hours. After cooling to room temperature, 40 times the mass of n-hexane of 2-amino-4-hydroxy-6-methylpyrimidine is added and stirred at room temperature for 6 hours. The mixture is then filtered using a sand filter. The resulting filter residue is washed with n-hexane, and the above operation is repeated until no hexamethylene diisocyanate residue remains in the filtrate. The filter residue is then mixed with 4-aminophenylboronic acid pinacol ester and chloroform, wherein the molar ratio of hexamethylene diisocyanate trimer to 4-aminophenylboronic acid pinacol ester is 1:1, and the chloroform... The mixture was mixed with the filter residue at a mass ratio of 1.9:16 and stirred at 60°C for 12 hours. After cooling to room temperature, it was vacuum filtered using a sand core filter to obtain secondary filter residue. The secondary filter residue and chloroform were mixed evenly at a mass ratio of 1:60. Then, E51 epoxy resin was added, with the molar ratio of hydroxyl groups in the epoxy resin to isocyanates in the secondary filter residue being 1:1.2. Dibutyltin dilaurate (0.1 times the mass of the secondary filter residue) was added, and the mixture was stirred and refluxed at 60°C for 24 hours. After naturally cooling to room temperature, chloroform (100 times the mass of the secondary filter residue) was added and mixed and diluted. The mixture was allowed to stand for 12 hours. The lower layer solution was removed, and chloroform (150 times the mass of the secondary filter residue) was added and allowed to stand for 24 hours. The lower layer solution was removed again, and this process was repeated 5 times. The remaining solution was then evaporated using a rotary evaporator to remove the chloroform solvent, yielding the modified epoxy resin.
[0050] The composite filler is prepared as follows: At 25°C, aluminum isopropoxide, ethyl acetoacetate, and ethanol are ultrasonically mixed in a molar ratio of 1:1:5 for 10 min. The mixture is then poured into 85°C hot water at 300 r / min at a volume of 200 times that of aluminum isopropoxide. The temperature and stirring rate are kept constant. After stirring for 30 min, the pH is adjusted to 3.5 by adding 68% nitric acid. The mixture is then allowed to cool naturally to room temperature. Next, isopropanol is added in a volume of 1.5 times that of aluminum isopropoxide. Stirring continues, followed by the sequential addition of modified boron nitride and silane coupling agent. The molar ratio of aluminum isopropoxide to silane coupling agent is 1:3, and the mass ratio of aluminum isopropoxide to modified boron nitride is 1:0.4. Stirring continues for 4 h to obtain the composite filler.
[0051] The modified boron nitride is prepared as follows: hydroxylated boron nitride is added to a high-speed mixer and stirred at 2000 rpm for 40 min at 75 °C. Then, an aluminate coupling agent is added and stirring is continued for 4 h to obtain modified boron nitride.
[0052] The mass ratio of the aluminate coupling agent to the hydroxylated boron nitride is 0.03:1.
[0053] The preparation method of the hydroxylated boron nitride is as follows: Hexagonal boron nitride powder and sodium cholate powder are added to deionized water and mixed, wherein the mass ratio of hexagonal boron nitride powder, sodium cholate powder and deionized water is 1:0.01:40. Then, the mixture is placed in an ultrasonic cell disruptor and treated with ultrasound at 600W for 3.5h. After the ultrasound is completed, the mixture is centrifuged at 3000r / min for 12min. The bottom precipitate is then removed, and the upper suspension is taken and dried in an oven at 60℃ to obtain hydroxylated boron nitride.
[0054] Comparative Example 1
[0055] The only difference between Comparative Example 1 and Example 2 is that the composite epoxy resin is obtained by mixing and reacting hexamethylene diisocyanate trimer, 4-aminophenylboronic acid pinacol ester, and epoxy resin. The remaining steps and components are the same as in Example 2.
[0056] Comparative Example 2
[0057] The only difference between Comparative Example 2 and Example 2 is that the composite epoxy resin is obtained by mixing and reacting 2-amino-4-hydroxy-6-methylpyrimidine, hexamethylene diisocyanate, pinacol 4-aminophenylboronic acid, and epoxy resin; the remaining steps and components are the same as in Example 2.
[0058] Comparative Example 3
[0059] The only difference between Comparative Example 3 and Example 2 is that the composite epoxy resin is obtained by mixing and reacting 2-amino-4-hydroxy-6-methylpyrimidine, hexamethylene diisocyanate trimer, and epoxy resin. The remaining steps and components are the same as in Example 2.
[0060] Comparative Example 4
[0061] The only difference between Comparative Example 4 and Example 2 is that epoxy resin is used to prepare powder coating for electric drive systems of new energy vehicles; the remaining steps and components are the same as in Example 2.
[0062] Comparative Example 5
[0063] The only difference between Comparative Example 5 and Example 2 is that the composite filler is obtained by mixing and reacting aluminum isopropoxide, ethyl acetoacetate, ethanol, boron nitride, and silane coupling agent; the remaining steps and components are the same as in Example 2.
[0064] Comparative Example 6
[0065] The only difference between Comparative Example 6 and Example 2 is that the composite filler is obtained by mixing and reacting aluminum isopropoxide, ethyl acetoacetate, ethanol, and modified boron nitride; the remaining steps and components are the same as in Example 2.
[0066] Comparative Example 7
[0067] The only difference between Comparative Example 7 and Example 2 is that the composite filler is obtained by mixing and reacting modified boron nitride and silane coupling agent; the remaining steps and components are the same as in Example 2.
[0068] Comparative Example 8
[0069] The only difference between Comparative Example 8 and Example 2 is that boron nitride was used to prepare the powder coating for the electric drive system of new energy vehicles; the remaining steps and components are the same as in Example 2.
[0070] Example of effect
[0071] Table 1 below shows the performance test standards and evaluation indicators for powder coatings used in electric drive systems of new energy vehicles:
[0072] Table 1
[0073]
[0074] Table 2 below shows the performance test and analysis results of the powder coatings for electric drive systems of new energy vehicles prepared using Examples 1-3 and Comparative Examples 1-8 of the present invention.
[0075] Table 2
[0076]
[0077] Table 2 shows that the powder coatings for new energy vehicle electric drive systems prepared in the examples exhibit good insulation, impact resistance, damp heat resistance, thermal stability, flame retardancy, and hardness. Comparing Example 2 with Comparative Examples 1, 2, 3, and 4, it is found that the powder coatings for new energy vehicle electric drive systems prepared using a composite epoxy resin obtained by mixing 2-amino-4-hydroxy-6-methylpyrimidine, hexamethylene diisocyanate trimer, 4-aminophenylboronic acid pinacol ester, and epoxy resin exhibit good insulation, impact resistance, damp heat resistance, thermal stability, flame retardancy, and hardness. Comparing Example 2 with Comparative Examples 5, 6, 7, and 8, it is found that the composite filler obtained by mixing aluminum isopropoxide, ethyl acetoacetate, ethanol, modified boron nitride, and silane coupling agent to prepare the powder coatings for new energy vehicle electric drive systems exhibit good insulation, impact resistance, damp heat resistance, thermal stability, flame retardancy, and hardness.
[0078] It should also be noted that the various specific technical features described in the above embodiments can be combined in any suitable manner without contradiction. To avoid unnecessary repetition, the present invention will not describe the various possible combinations separately.
Claims
1. A powder coating for electric drive system of new energy vehicles, characterized in that: The raw material components include, by weight: 50 to 80 parts of composite epoxy resin, 10 to 20 parts of composite filler, 2 to 4 parts of curing agent, 0.2 to 0.8 parts of imidazole accelerator, 1 to 2 parts of leveling agent, 0.8 parts of wax powder, 0.3 to 0.9 parts of benzoin, and 1 to 5 parts of pigment; The composite epoxy resin is obtained by a mixed reaction of 2-amino-4-hydroxy-6-methylpyrimidine, hexamethylene diisocyanate trimer, 4-aminophenylboronic acid pinacol ester and epoxy resin, wherein the amino groups on 2-amino-4-hydroxy-6-methylpyrimidine and 4-aminophenylboronic acid pinacol ester react with part of the isocyanate on the hexamethylene diisocyanate trimer, and the remaining isocyanate groups react with the hydroxyl groups in the epoxy resin to form a composite epoxy resin with a main chain containing UPy groups, isocyanurate six-membered heterocyclic rings and phenylboronic acid pinacol ester on the side chains of the epoxy resin molecular chain; The composite filler is obtained by mixing aluminum isopropoxide, ethyl acetoacetate, ethanol, modified boron nitride, and a silane coupling agent; the modified boron nitride is boron nitride modified by an aluminate coupling agent; the aluminate coupling agent is isopropyl distearoyloxy aluminate; Among them, the -(CH2) 16 The CH3 functional group is entangled with the molecular chain on the composite epoxy resin; the phenylboronic acid pinacol ester in the composite epoxy resin is hydrolyzed to obtain phenylboric acid, and the phenylboric acid reacts with the silanol group in the composite filler to form polysiloxane.
2. A method for preparing a powder coating for a new energy vehicle electric drive system as claimed in claim 1, characterized in that: The method comprises the following preparation steps: Add 50-80 parts by weight of composite epoxy resin to a sand mill dispersing and stirring multi-purpose machine, add 10% hydrochloric acid solution to a pH of 1, disperse at 2000-3000 r / min for 1 hour, then continue to drop 25% NaOH solution to a pH of 13, continue to disperse for 1 hour, let stand, remove the upper solution, then continue to add hydrochloric acid, 10% hydrochloric acid solution to a pH of 5, spin dry, add it together with 10-20 parts by weight of composite filler to a sand mill dispersing and stirring multi-purpose machine, heat up To 80 ° C and disperse at 2000-3000 r / min for 8 hours, naturally cool to room temperature, add 2-4 parts by mass of curing agent, 0.2-0.8 parts by mass of imidazole accelerator, 1-2 parts by mass of leveling agent, 0.8 parts by mass of wax powder, 0.3-0.9 parts by mass of benzoin, 1-5 parts by mass of pigment, continue to disperse for 30 minutes, then put into a twin-screw extruder for extrusion, cool and crush, and then use a high-speed crusher to crush, pass through a 180-mesh standard sieve, and obtain a powder coating for the electric drive system of new energy vehicles.
3. The method for preparing powder coating for electric drive system of new energy vehicle according to claim 2, characterized in that: The preparation method of the composite epoxy resin is as follows: under nitrogen protection and anhydrous conditions, 2-amino-4-hydroxy-6-methylpyrimidine and hexamethylene diisocyanate trimer are mixed in a molar ratio of 1:1, then heated to 60°C, vacuumed at a stirring speed of 150rpm until no bubbles are generated on the liquid surface, then heated to 90°C and stirred for reaction for 26 hours, cooled to room temperature, added with n-hexane 20 to 40 times the mass of 2-amino-4-hydroxy-6-methylpyrimidine, stirred at room temperature for 4 to 6 hours, and then filtered with a sand core filter device, the obtained filter residue is continuously washed with n-hexane, and the above operation is repeated until no hexamethylene diisocyanate remains in the filtrate, and then the filter residue is mixed with 4-aminophenylboronic acid pinacol ester and chloroform, wherein the molar ratio of hexamethylene diisocyanate trimer to 4-aminophenylboronic acid pinacol ester is 1:1, and the molar ratio of chloroform to the filter residue is 1:
1. The mixture is stirred at a mass ratio of 1.7 to 1.9:15 to 16, stirred at 60°C for 12 hours, and continued to cool to room temperature. The secondary filter residue and chloroform are vacuum filtered with a sand core filter device to obtain a secondary filter residue. The secondary filter residue and chloroform are stirred and mixed at a mass ratio of 1:50 to 60, and then E51 epoxy resin is added. The molar ratio of hydroxyl in the epoxy resin to isocyanate in the secondary filter residue is 1:1 to 1.
2. Dibutyltin dilaurate is added in an amount of 0.1 times the mass of the secondary filter residue, and stirring and refluxing at 60°C are continued for 24 hours. Naturally cool to room temperature, chloroform is added in an amount of 100 times the mass of the secondary filter residue to mix and dilute, and then stand for 12 hours. After taking out the lower layer solution, chloroform is added in an amount of 150 times the mass of the secondary filter residue and stood for 24 hours. The lower layer solution is continued to be taken out. After repeating 5 times, the chloroform solvent is removed from the remaining solution by a rotary evaporator to obtain a composite epoxy resin.
4. The method for preparing a powder coating for a new energy vehicle electric drive system according to claim 2, characterized in that: The preparation method of the composite filler is as follows: at 25°C, aluminum isopropoxide, ethyl acetoacetate and ethanol are ultrasonically mixed in a molar ratio of 1:1:5 for 10 minutes, poured into 85°C hot water with a volume of 200 times the volume of the aluminum isopropoxide substance at a speed of 250-300 r / min, the temperature and stirring rate are kept constant, after stirring for 30 minutes, a pH value is adjusted to 3.2-3.5 by adding 68% of the concentration of aluminum isopropoxide, naturally cooled to room temperature, then isopropanol with a volume of 1.5 times the volume of the aluminum isopropoxide substance is added, stirring is continued, and then modified boron nitride and silane coupling agent are added in sequence, wherein the molar ratio of aluminum isopropoxide to the silane coupling agent is 1:3, and the mass ratio of aluminum isopropoxide to the modified boron nitride is 1:0.2-0.4, stirring is continued for 2-4 hours, and the composite filler is obtained.
5. The method for preparing powder coating for electric drive system of new energy vehicle according to claim 4, characterized in that: The preparation method of the modified boron nitride is as follows: hydroxylated boron nitride is added to a high-speed stirrer, stirred at 75°C at 1500-2000 rpm for 20-40 minutes, then an aluminate coupling agent is added, and stirring is continued for 2-4 hours to obtain modified boron nitride.
6. The method for preparing powder coating for electric drive system of new energy vehicle according to claim 5, characterized in that: The mass ratio of the aluminate coupling agent to the hydroxylated boron nitride is 0.01-0.03:
1.
7. The method for preparing powder coating for electric drive system of new energy vehicle according to claim 5, characterized in that: The preparation method of the hydroxylated boron nitride is as follows: hexagonal boron nitride powder and sodium cholate powder are added into deionized water and mixed, wherein the mass ratio of the hexagonal boron nitride powder, the sodium cholate powder and the deionized water is 1:0.01:40, and then the mixture is placed into an ultrasonic cell crusher and subjected to 600W ultrasonic treatment for 2.5 to 3.5 hours. After the ultrasonic treatment, the mixture is centrifuged at a speed of 3000 r / min for 8 to 12 minutes in a centrifuge, and then the bottom precipitate is removed, and the upper suspension is taken and dried in an oven at 60°C to obtain hydroxylated boron nitride.
Citation Information
Patent Citations
Method for preparing photic driving self-repair film based on ethylene-butylene copolymer
CN106221100A
Preparation method of epoxy resin composite material based on quadruple hydrogen bond supermolecular self repairing
CN108715667A